The circular nature of recurrent life cycle events: a test comparing tropical and temperate phenology - Staggemeier, Vanessa Graziele; Camargo, Maria Gabriela Gutierrez; Diniz‐Filho, José Alexandre Felizola; Freckleton, Robert; Jardim, Lucas; Morellato, Leonor Patrícia Cerdeira; Stott, Iain (The Journal of ecology, 2020)
The high diversity of plant species in the tropics has revealed complex phenological patterns and reproductive strategies occurring throughout the year. Describing and analysing tropical plant phenology, and detecting triggers, demands to consider the circular nature of recurrent life cycle events and the use of appropriated statistical metrics. Here, we explore analytical pitfalls potentially affecting results of studies that do not consider the circular nature of phenology data when comparing resting and non‐resting systems, especially when accounting for phylogeny. We discuss definitions of the widely used first flowering date and revisit the literature on phylogenetic signal in plant phenology. We compare statistical analyses for tropical and temperate phenology by simulating communities with known phenological and phylogenetic structures. We demonstrate that ignoring the circular nature of phenological data underestimates the phylogenetic signal in plant phenology. Using the proposed circular transformation for non‐resting tropical ecosystems and resting temperate systems prevented errors, yielding precise comparisons. Synthesis. The analysis of both non‐resting and resting systems must consider the circularity of phenological events. Circular statistics is the appropriate approach to calculate phenological parameters, identify phylogenetic signal and assess drivers, allowing accurate cross‐comparisons of phenology across environments at large spatial scales. Foreign Language  Resumo A elevada diversidade de espécies vegetais nos trópicos tem revelado padrões fenológicos e estratégias reprodutivas complexas ocorrendo no decorrer do ano todo. Descrever e analisar a fenologia de plantas tropicais e detectar seus gatilhos demanda considerar a natureza circular dos eventos recorrentes do ciclo de vida e o uso de métricas estatísticas apropriadas. Aqui nós exploramos as armadilhas analíticas que podem afetar negativamente resultados de estudos com fenologia em sistemas tropicais sem estação de repouso (espécies reproduzindo ao longo do ano todo) e temperados com estação de repouso (onde é possível definir o início da reprodução da comunidade), especialmente quando considerando o método filogenético comparativo. Nós discutimos as definições do parâmetro amplamente usado ‐ primeira data de floração ‐ e revisitamos a literatura sobre sinal filogenético na fenologia de plantas. Nós comparamos as técnicas estatísticas empregadas para analisar fenologia em ambientes tropicais e temperados simulando comunidades com estruturas fenológicas e filogenéticas conhecidas. Nós demonstramos que ignorar a natureza circular do dado fenológico subestima a influência do sinal filogenético na fenologia vegetal. Aplicar a mesma transformação circular para ecossistemas tropicais sem estação de repouso e para sistemas temperados com estação de repouso previne erros e permite comparações precisas. Síntese. A análise de sistemas com ou sem estação de repouso deve considerar a circularidade dos eventos fenológicos. Estatística circular é a abordagem apropriada para calcular parâmetros fenológicos bem como para avaliar sinal filogenético e fatores afetando a fenologia, porque ela permite comparações acuradas da fenologia entre ambientes em grandes escalas espaciais. The analysis of both non‐resting and resting systems must consider the circularity of phenological events. Circular statistics is the appropriate approach to calculate phenological parameters, identify phylogenetic signal and assess drivers, allowing accurate cross‐comparisons of phenology across environments at large spatial scales.